Antinociceptive and anti-inflammatory activities of the aqueous extract of Kaempferia galanga leaves in animal models. - Sulaiman, Mohd Roslan; Zakaria, Zainul Amiruddin; Israf Ali, Daud Ahmad; Ng, F. N.; Ng, Y. C.; Baharuldin, Mohamad Taufik Hidayat (Springer Verlag, 2008)
This study was performed to determine the antinociceptive and anti-inflammatory activities of aqueous extract of Kaempferia galanga leaves using various animal models. The extract, in the doses of 30, 100, and 300 mg/kg, was prepared by soaking (1:10; w/v) the air-dried powdered leaves (40 g) in distilled water (dH2O) for 72 h and administered subcutaneously in mice/rats 30 min prior to the tests. The extract exhibited significant (P < 0.05) antinociceptive activity when assessed using the abdominal constriction, hot-plate and formalin tests, with activity observed in all tests occurring in a dose-dependent manner. Furthermore, the antinociceptive activity of K. galanga extract was significantly (P < 0.05) reversed when prechallenged with 10 mg/kg naloxone. The extract also produced a significantly (P < 0.05) dose-dependent anti-inflammatory activity when assessed using the carrageenan-induced paw-edema test. In conclusion, this study demonstrated that K. galanga leaves possessed antinociceptive and anti-inflammatory activities and thus supports the Malay's traditional uses of the plant for treatments of mouth ulcer, headache, sore throat, etc.